Validity and reliability of intra-stroke kayak velocity and acceleration using a GPS-based accelerometer - Janssen, I.; Sachlikidis, A. (Sports Biomechanics, 2010)
The aim of this study was to assess the validity and reliability of the velocity and acceleration measured by a kayak-mounted GPS-based accelerometer units compared to the video-derived measurements and the effect of satellite configuration on velocity. Four GPS-based accelerometers units of varied accelerometer ranges (2 g or 6 g) were mounted on a kayak as the paddler performed 12 trials at three different stroke rates for each of three different testing sessions (two in the morning vs. one in the afternoon). The velocity and acceleration derived by the accelerometers was compared with the velocity and acceleration derived from high-speed video footage (100 Hz). Validity was measured using Bland and Altman plots, R2, and the root of the mean of the squared difference (RMSe), while reliability was calculated using the coefficient of variation, R2, and repeated measures analysis of variance (ANOVA) tests. The GPS-based accelerometers under-reported kayak velocity by 0.14-0.19 m/s and acceleration by 1.67 m/s2 when compared to the video-derived measurements. The afternoon session reported the least difference, indicating a time of day effect on the velocity measured. This study highlights the need for sports utilising GPS-based accelerometers, such as minimaxX, for intra-stroke measurements to conduct sport-specific validity and reliability studies to ensure the accuracy of their data.